2021
DOI: 10.1016/j.joei.2020.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic fast Co-Pyrolysis of sewage sludge−sawdust using mixed metal oxides modified with ZSM-5 catalysts on dual-catalysts for product upgrading

Abstract: Catalytic fast co-pyrolysis of sewage sludge and sawdust was performed using Py/GC-MS for pyrolytic product upgrades. Metal oxides (NiO and MoO3) and ZSM-5 catalysts had been introduced into single catalytic pyrolysis. The combination of NiO + MoO3 in mixed metal oxides (MMOs) was modified with ZSM-5 under a dual-catalyst with different catalytic layouts. In the pyrolysis process, the metal oxides specifically promoted the formation of phenols, ketones, and furans. ZSM-5 was proven to be more effective in prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Some studies also reported that Ni has a high affinity leading to coke formation [2,6,10]. Haji Morni et al [11] modified the ZSM-5 using nickel (Ni) and molybdenum (Mo) for the co-pyrolysis of sewage sludge−sawdust. It was reported that MoO 3 could reduce the aromatic compounds.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies also reported that Ni has a high affinity leading to coke formation [2,6,10]. Haji Morni et al [11] modified the ZSM-5 using nickel (Ni) and molybdenum (Mo) for the co-pyrolysis of sewage sludge−sawdust. It was reported that MoO 3 could reduce the aromatic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that MoO 3 could reduce the aromatic compounds. However, incorporating NiO with MoO 3 could massively increase the aromatic compounds, as well as the oxygenated compounds [11]. Botas et al [10] reported that the Mo-modified nanocrystalline ZSM-5 zeolite could increase the aromatic compounds on the catalytic conversion of rapeseed oil.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation